Perkembangan Bahasa pada Anak Usia 3-4 Tahun - Indah Lestari (Perkumpulan Kualitama Edukatika Indonesia, 2021)
The purpose of this study was to determine the language development of children aged 3 years. This type of research is descriptive qualitative, this research information obtained from the closest family of children, namely parents and relatives. The data collection tools in this study were in the form of observation, interviews and documentation. While the data that has been collected is then analyzed with qualitative descriptive data analysis techniques, namely data reduction, data presentation and conclusion drawing (verification). The results of the research are the language development of children aged 3 years including: First, phonetics, namely the sound of language. Second, Morphology, namely changes in word form, and changes in word form to the meaning and group of words. Third Syntax, namely Ordering words in determining the meaning which is composed of Subject, Predicate, Object and Description. Fourth, Semantics is Knowing the meanings or meanings contained in each word in other words. And Fifth Pragmatics, namely Using polite language in appropriate situations. And the results of the achievements of the five aspects of language development of children aged 3 years that almost all indicators are achieved very well. Only pragmatic development indicators are still sufficient or are starting to develop. As for the overall results of the development of language knowledge, children aged 3-4 years can be said to have developed well.